Social and Moral Guidance of Balinese Life in Kakawin Niti Sastra - Ida Bagus Putra Setiawan (Bali Tourism Journal, 2023)
Estimated to be written in 350 B.C. In the Magada Kingdom of India, Niti Sastra is one of the knowledge references that gives readers an overview of leadership and management. In Bali, the script is better known as Kakawin Niti Sastra. Kakawin is poetry written in the Kawi language, an extinct old Javanese language. Niti Sastra is the Sanskrit term for "science of morality," and it refers to the study of how to uphold Dharma or morality in one's conduct and in all of life. Politics and leadership are generally discussed in academia, as per Niti Sastra. After that, it gives a general summary of how the teachings of the Niti Sastra relate to those of other Hindu texts and goes on to describe the Ramayana and Mahabharata Epics in more detail. However, a closer look reveals that Niti Sastra also further documents and outlines social communication processes. Ideas given in the Kekawin Niti Sastra, particularly those pertaining to the arena of social life, have universal values, as evidenced by the presentation of several examples, even in a nation that no longer has a feudal administration system and its socioeconomic conditions. These principles, which are founded on Hinduism, still hold true. Thus, the Niti Sastra Book might be a good resource for academics looking to gain a deeper understanding, particularly about the application of moral principles to daily life.